ChemInform Abstract: Synthesis of allo‐ and epi‐Inositol via the NHC‐Catalyzed Carbocyclization of Carbohydrate‐Derived Dialdehydes. Issue 48 (2nd December 2014) - Stockton, Kieran P.; Greatrex, Ben W.; Taylor, Dennis K.
Abstract This describes the synthesis of allo‐inositol (IV) as well as a similar synthesis of epo‐inositol.